Pengaruh Strategi Manajemen Konflik Terhadap Kinerja Tim: Studi Kasus di Industri Hotel Khas - Henry Yuliamir; Renny Aprilliyani; Umar Abdul Jabbar (Jurnal Visi Manajemen, 2025)
This research aims to investigate the relationship between conflict management strategies and team performance in the Khas Hotel industry. Against the backdrop of the unique team dynamics and potential for conflict in the hospitality environment, this research focuses on deeper understanding to improve the effectiveness of conflict management and team performance. The research method used is a mixed approach, combining quantitative and qualitative analysis. Through surveys and interviews with hotel managers and staff, data was collected and analyzed to identify patterns and relationships between the variables studied. The research findings indicate an influence between implemented conflict management strategies and team performance, with important implications for practitioners in the hospitality industry in improving human resource management and team productivity.